Evaluation of confined masonry walls with varying sizes of confining elements and reinforcement ratios against cyclic loading. (1st June 2022) - Ibrar, Muhammad; Naseer, Amjad; Ashraf, Mohammad; Badshah, Eid; Ullah, Shahid
Abstract: This paper presents a study on the seismic evaluation of a typical 225 mm thick confined brick masonry wall with varying sizes of confining elements and reinforcement ratios in the confining elements. Eight specimens consisting four types of confined masonry walls have been selected. Two specimens were fabricated for each type of confined masonry wall. Transverse reinforcement details were kept constant and the same types of burnt clay bricks, concrete and mortar were used in all types of walls. These walls were tested under constant vertical and cyclic horizontal load in displacement-controlled environment to investigate their lateral strength, stiffness, ductility, and cracking patterns. It was found that by increasing the size of the confining elements from 75 mm to 150 mm, lateral strength, ductility and initial stiffness of the confined brick masonry walls increased by more than 15%, 9%, and 4.5%, respectively. Increasing the reinforcement ratio of the confining elements did not affect the lateral strength and cracking pattern of confined brick masonry walls, however, the initial stiffness and ductility were found marginally increased. Highlights: Thickness of confining element in confined masonry increases lateral strength, ductility, and stiffness. Crack pattern changes with change in the thickness of confining element. Longitudinal reinforcement ratio in confining element has less effect on the lateral strength of confined masonry.